Googling immigration: The associations between search behavior, immigration levels and migration attitudes - Álvaro Mariscal de Gante Martín (Revista Obets)
Google Trends has garnered scholarly attention for its application in fields such as disease spread, consumption patterns, or voting behavior. However, research concerning ethnic attitudes is limited, with most literature concentrating on racist searches in the United States, thereby neglecting immigration and European contexts. Furthermore, no previous studies have contrasted search patterns with explicit survey measures of racial or antiimmigrant prejudice. This study intends to fill these gaps by examining the case of Spain to explore whether and which Google searches about immigration are associated with migration attitudes and/or immigration levels. Based on a panel region-level database from 2010 to 2022, we applied Fixed-Effects OLS regression models to contrast search behavior with European Social Survey and/or Spanish Population register data. Queries related to immigrants are significantly more prevalent in areas with higher proportions of immigrants that are often othered. Furthermore, queries concerning the number of people of in the country are consistently associated with restrictive migration policy preferences regarding immigrant influxes, in line with longstanding survey research on negative attitudes and perceived demographic threat. Even if prone to false positives, this suggests that a surge in certain queries regarding immigrant volumes could serve as a useful, free, real-time tool for detecting potential shifts regarding restrictive immigration policy preferences.